Biodiversity of Local Vitis vinifera L. Germplasm: A Powerful Tool Toward Adaptation to Global Warming and Desired Grape Composition - Frioni, Tommaso; Bertoloni, Giovanni; Squeri, Cecilia; Garavani, Alessandra; Ronney, Lily; Poni, Stefano; Gatti, Matteo (Frontiers in Plant Science, 2020)
Global warming is endangering maintenance of optimal grape composition in white varietals aimed at sparkling wine making due to difficulties to maintain adequate acidity and fresh aromas. These troubles are being faced by the main white varietal of the Colli Piacentini district, named Ortrugo. Its vegetative and reproductive behavior was compared over 3 years with that of other minor autochthonous white varietals. Criteria set for adequate grape composition under sparkling vinification (total soluble solids at 20–21°Brix) and titratable acidity (TA) ≥ 6.5 g/L combined with Principal Component Analysis (PCA) on the measured variables allowed a thinnning down of the initial group of 17 to 7 varietals including Ortrugo, Bucalò, Barbesino, Lecco, Melara, Santa Maria and Molinelli. PCA isolated Ortrugo’s behavior for inadequacy to maintain sufficient TA at harvest mostly due to extremely low malic acid concentration. However, time trend analyses of accumulation and degradation patterns of tartaric and malic acids disclosed that, in Ortrugo, the most limiting factors were more intense post-veraison tartaric acid dilution and a lower malic acid pool at veraison as compared to any other varietal. Conversely, Molinelli and Barbesino proved to be ideal material for sparkling wine purposes, as they associated to desirable agronomic features a strong ability to retain high TA with a well-balanced tartrate-to-malate ratio. Our study emphasizes that often neglected or superficially evaluated germplasm genetic resources might hide strong potential for adapting to challenges imposed by climate change in that representing an excellent tool for adaptation strategies.